Pengaruh Program Bantuan Stimulan Perumahan Swadaya (BSPS) Pada Masyarakat di Kelurahan Lowulowu Kecamatan Lealea Kota Baubau - Kuflia Muak Hara (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2019)
The house renovation program is one of the programs of the government in an effort to provide protection to poor families in order to improve the level of welfare of poor families. This program is carried out in the form of providing building materials along with builders and technicians to build or renovate homes that are not livable and do not meet the health requirements of being livable. This study aims to address the research problem of the socio-economic and environmental impacts of a government program called Self-Help Housing Stimulant Assistance (BSPS) for low-income people in the City of Baubau especially in Sub-Lowulowu. The BSPS program provides a fairly good change and impact. The BSPS program improves the quality of residents' homes and increases welfare.